#### Answer

t=$\frac{A-P}{Pr}$

#### Work Step by Step

A=P+Prt
P+Prt=A
Prt=A-P
$\frac{Prt}{Pr}$=$\frac{A-P}{Pr}$
t=$\frac{A-P}{Pr}$

Published by
Pearson

ISBN 10:
0-13417-805-X

ISBN 13:
978-0-13417-805-9

t=$\frac{A-P}{Pr}$

A=P+Prt
P+Prt=A
Prt=A-P
$\frac{Prt}{Pr}$=$\frac{A-P}{Pr}$
t=$\frac{A-P}{Pr}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.